A Genome-Wide Screen Identifies Factors Involved in S. aureus-Induced Human Neutrophil Cell Death and Pathogenesis - Yang, Dingyi; Ho, Yin Xin; Cowell, Laura M.; Jilani, Iqra; Foster, Simon J.; Prince, Lynne R. (Frontiers in Immunology, 2019)
Staphylococcus aureus is a commensal organism in approximately 30% of the human population and colonization is a significant risk factor for invasive infection. As a result of this, there is a great need to better understand how S. aureus overcomes human immunity. Neutrophils are essential during the innate immune response to S. aureus, yet this microorganism uses multiple evasion strategies to avoid killing by these immune cells, perhaps the most catastrophic of which is the rapid induction of neutrophil cell death. The aim of this study was to better understand the mechanisms underpinning S. aureus-induced neutrophil lysis, and how this contributes to pathogenesis in a whole organism model of infection. To do this we screened the genome-wide Nebraska Transposon Mutant Library (NTML) in the community acquired methicillin resistant S. aureus strain, USA300, for decreased ability to induce neutrophil cell lysis. Out of 1,920 S. aureus mutants, a number of known regulators of cell lysis (including the master regulators accessory gene regulator A, agrA and Staphylococcus exoprotein expression protein S, saeS) were identified in this blinded screen, providing validity to the experimental system. Three gene mutations not previously associated with cell death: purB, lspA, and clpP were found to be significantly attenuated in their ability to induce neutrophil lysis. These phenotypes were verified by genetic transductants and complemented strains. purB and clpP were subsequently found to be necessary for bacterial replication and pathogenesis in a zebrafish embryo infection model. The virulence of the clpP mutant was restored in a neutrophil-depleted zebrafish model, suggesting the importance of ClpP in mechanisms underpinning neutrophil immunity to S. aureus. In conclusion, our work identifies genetic components underpinning S. aureus pathogenesis, and may provide insight into how this commensal organism breaches innate immune barriers during infection.